2018
DOI: 10.1111/jon.12512
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Etiology of Microinfarcts in Patients with Ischemic Stroke

Abstract: CMIs occurring within the vascular territory of a larger infarct are more likely embolic, but those occurring outside are probably related to SVD. Our findings suggest a role for SVD in pathogenesis of CMIs and emphasize the importance of etiologic workup to identify alternate etiologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…[39][40][41] Apart from lacunes of presumed vascular origin, we did not find associations with CSVD markers such as WMH, microbleeds or brain atrophy. Associations of CMIs with WMH have been found in several studies, [12][13][14] but were absent in others. [6][7][8]37 Associations with cerebral microbleeds were similarly inconsistent, 7,8,11,12,14 as are the few results for brain atrophy.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…[39][40][41] Apart from lacunes of presumed vascular origin, we did not find associations with CSVD markers such as WMH, microbleeds or brain atrophy. Associations of CMIs with WMH have been found in several studies, [12][13][14] but were absent in others. [6][7][8]37 Associations with cerebral microbleeds were similarly inconsistent, 7,8,11,12,14 as are the few results for brain atrophy.…”
Section: Discussionmentioning
confidence: 98%
“…17 Furthermore, CMIs' associations with risk factors such age, sex, smoking, alcohol use, hypertension, hyperlipidemia, and diabetes, are similarly inconsistent. [6][7][8][11][12][13][14] In addition, CMIs have been associated with ante mortem cognitive decline and dementia in autopsy studies. 2 A few neuroimaging studies have found similar associations in vivo.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…All MRI images were independently rated by one primary rater (AS) as well as one secondary rater (JOF, FS, AM). The primary rater (AS) has previously demonstrated excellent interrater (AS and JOF; n = 40) agreement for the presence (Κ = 0.82, p < 0.001) and number (intraclass correlation coefficient = 0.85, p < 0.001) of DWIHLs [22]. The raters were blinded to baseline features, randomization, and outcomes.…”
Section: Imaging Acquisition and Analysismentioning
confidence: 99%